Microwave processing technology for food safety and quality: A review - Nguyen, Tien Phung; Songsermpong, Sirichai (Agriculture and Natural Resources, 2022)
Microwave processing is a novel heating method which has been applied in the industrial and agricultural sectors, especially in the food industry. The use of microwave heating presents many advantages involving rapid heating, high temperature, short cooking time, clean energy and low operating cost. In addition, this technique can improve the safety and qualities of food products. This paper discusses industrial and domestic microwave applications, including sterilization, pasteurization, thawing, puffing, atmospheric drying, vacuum drying, freeze drying, blanching, frying, baking and extraction processes, applied in various types of foods from the viewpoint of quality and safety. Food innovations based on microwave technology are presented. Microwave technology is predicted as a first alternative technology and to become more popular in the near future.